Correction: Simionescu et al. The Multifaceted Role of Extracellular Vesicles in Glioblastoma: microRNA Nanocarriers for Disease Progression and Gene Therapy. Pharmaceutics 2021, 13, 988 - Natalia Simionescu; Radu Zonda; Anca Roxana Petrovici; Adriana Georgescu (MDPI AG, 2024)
In the original publication [...]